Developing STEAM Educational Scenarios in Pedagogical Studies using Robotics: An Undergraduate Course for Elementary School Teachers - Xefteris, S. (Engineering, Technology & Applied Science Research, 2021)
In recent years we have observed a clear trend for the transformation and evolution of teaching practices using Information and Communication Technologies (ICT) and in particular educational robotics. As modern society gives great importance to scientific and technological literacy and new technologies, the educational process must play a central role in the development of the respective skills. Thus, the training of future teachers in corresponding fields is especially important. In this paper, we present the curriculum design of a course named "S.T.E.A.M Teaching Scenarios using Educational Robotics" implemented for undergraduate pre-service teachers at the Elementary Education Department of the University of Western Macedonia in Florina, Greece. The objectives of the course include the development of critical and computational thinking, familiarity with robots, and the process of their integration in curricula focusing on interdisciplinary practices facilitated by embodied learning affordances.